Influence of environmental values on the typhoon risk perceptions of high school students: a case study in Ningbo, China - Yao, Lianying; Shen, Jinchi; Zhang, Fuying; Gu, Xinbing; Jiang, Shuli (MDPI AG, 2021)
Typhoon is a severe natural disaster that would bring huge economic losses and casualties to society. High school students are more vulnerable compared with adults during typhoon. Improving risk perception of typhoon can assist high school students effectively respond to typhoon and reduce related losses. Environmental values play an important role in human’s perceptions and actions. Although typhoon is related with environment, few studies have investigated the influence of environmental values on typhoon risk perception of high school students. This study investigates typhoon risk perception of high school students in Ningbo, China, and further analyzes the influence of environmental values on the perception with structural equations model. Results reveal that environmental values have significantly positive impacts on the typhoon risk perception. The findings also demonstrate that disaster threats and the disaster management ability of the government have significant positive impacts on the typhoon risk perception. This study proposes suggestions and measures to improve the typhoon risk perception among high school students and provides a reference for typhoon prevention and reduction education in China.